Martin Luther King, Jr : a man who changed things - Greene, Carol (Chicago : Childrens Press, 1989)
A simple biography of the Baptist minister and civil rights leader who helped African Americans win many battles for equal rights and who was awarded the Nobel Peace Prize in 1964.
Multicultural Review.
2.6
K-3.
K-3
Keywords: King, Martin Luther, -- Jr., -- 1929-1968 -- Juvenile literature; King, Martin Luther, -- Jr., -- 1929-1968.; King, Martin Luther, Jr., -- 1929-1968.; African Americans -- Biography -- Juvenile literature; African Americans -- Civil rights -- Juvenile literature; Baptists -- United States -- Clergy -- Biography -- Juvenile literature; Civil rights workers -- United States -- Biography -- Juvenile literature; African Americans -- Biography; Civil rights workers; Clergy; African Americans -- Biography; Civil rights workers -- Biography; Clergy -- Biography